Species Delimitation of Hexacorallia and Octocorallia Around Iceland Using Nuclear and Mitochondrial DNA and Proteome Fingerprinting - Korfhage, Severin A.; Rossel, Sven; Brix, Saskia; McFadden, Catherine S.; Ólafsdóttir, Steinunn Hilma; Martínez Arbizu, Pedro (Frontiers in Marine Science, 2022)
Cold-water corals build up reef structures or coral gardens and play an important role for many organisms in the deep sea. Climate change, deep-sea mining, and bottom trawling are severely compromising these ecosystems, making it all the more important to document the diversity, distribution, and impacts on corals. This goes hand in hand with species identification, which is morphologically and genetically challenging for Hexa- and Octocorallia. Morphological variation and slowly evolving molecular markers both contribute to the difficulty of species identification. In this study, a fast and cheap species delimitation tool for Octocorallia and Scleractinia, an order of the Hexacorallia, of the Northeast Atlantic was tested based on 49 specimens. Two nuclear markers (ITS2 and 28S rDNA) and two mitochondrial markers (COI and mtMutS) were sequenced. The sequences formed the basis of a reference library for comparison to the results of species delimitation based on proteomic fingerprinting using MALDI-TOF MS. The genetic methods were able to distinguish 17 of 18 presumed species. Due to a lack of replicates, using proteome fingerprinting only 7 species were distinguishable. Species that could not be distinguished from one another still achieved good signals of spectra but were not represented by enough specimens for comparison. Therefore, it is predicted that with an extensive reference library of proteome spectra for Scleractinia and Octocorallia, MALDI-TOF MS may provide a rapid and cost-effective alternative for species discrimination in corals.